DINAMIKA PARTAI POLITIK DAN POSITIONING IDEOLOGI: STUDI TENTANG PERGESERAN POSITIONING IDEOLOGI PARTAI-PARTAI POLITIK PESERTA PEMILU 2014 - Yeby Ma'asan Mayrudin (Journal of Governance, 2017)
This article examines the phenomenon of shifting the ideologicalpositioning on political parties in the 2014 election. It’s also presents themapping of ideological positioning of parties. The main argument arecreated by the political parties in the 2014 election seemed to exercise ashiftting in ideological positioning. In addition, this research also succeededin characterizing the shifting typology of party in the 2014 election, at leastthere are three patterns: conservative, progressive conservatist, andextremist.